2015
DOI: 10.1089/apc.2014.0187
|View full text |Cite
|
Sign up to set email alerts
|

Improving Parental Stress Levels Among Mothers Living with HIV: A Randomized Control Group Intervention Study

Abstract: Limited knowledge exists regarding parenting efficacy interventions for mothers living with HIV (MLH). This study evaluated the impact of a supportive group intervention on lowering parenting stress among MLH. Eighty MLH were randomized to a parenting (N=34) or health focused (control) (N=46) group intervention. Pre- and post-intervention stress levels were assessed using the Parental Stress Index-Short Form (PSI/SF). Differences in PSI/SF scores were examined using ANOVA, and predictors of PSI/SF scores were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Table 1 includes a summary of the main characteristics of the thirteen studies included in this review. Ten interventions were implemented in the United States [14, 1623, 25]. Two interventions were conducted in China [25, 24] and one intervention was conducted in South Africa [13].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 includes a summary of the main characteristics of the thirteen studies included in this review. Ten interventions were implemented in the United States [14, 1623, 25]. Two interventions were conducted in China [25, 24] and one intervention was conducted in South Africa [13].…”
Section: Resultsmentioning
confidence: 99%
“…Children of parents living with HIV included in the studies ranged from 4 to 20 years old at the time of intervention. Two studies explicitly focused on PLH and their young children, ages 4–12 [13, 14]. One study focused explicitly on PLH and their adolescent children, ages 11–18 [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Murphy, Marelich, Armistead, Herbeck, and Payne (2010) found that MLWH reporting more stress in their parenting roles and personal health were less likely to engage their children in family routines and more likely to report poorer parent-child communication. Interventions targeting parenting stress and family interactions with MLWH and their children have demonstrated positive outcomes related to reduced stress (Johnson et al, 2015) and improved open communication (Murphy, Armistead, Marelich, Payne, & Herbeck, 2011). Although such behavioral interventions have shown promise in affecting change, little is known regarding the relationship between parenting stress and indicators of family functioning from the child’s perspective.…”
mentioning
confidence: 99%